Cross-cultural aspects in foreign languages learning - Mirochnik, Vira (My University, 2014)
The article deals with cross-cultural aspects in learning foreign languages as one of the components for the education of competent professionals.
Keywords: міжкультурна комунікація; вивчення іноземної мови; language learning; ділова іноземна мова; intercultural communication; business language; кафедра ділової іноземної мови та міжнародної комунікації